PENGARUH PEMBERIAN SLUDGE PADAT BIOGAS DARI FESES YANG BERBEDA SEBAGAI PUPUK ORGANIK TERHADAP PERTUMBUHANDAN PRODUKSI RUMPUT ODOT (Pennisetum purpureum cv. Mott - Mangonar Lumbantoruan (STOCK Peternakan, 2023)
This study aims to determine the effect of solid biogas sludge from different faeces as organic fertilizer on the growth and production of Odot grass (Pennisetum purpureum cv. Mott). This research was conducted in the experimental of the Faculty of Animal Husbandry, University of HKBP Nommensen in Simalingkar A Village, Medan Tuntungan District for 122 days (3 months 2 days). This study used biogas sludge as organic fertilizer and odot grass seeds which were planted on an area of 126 m2 consisting of 20 plots with an area of 3 m2 each, 1 m spacing between plots, and 50 cm × 100 cm plant spacing. Each plot consisted of 4 planting holes and 2 planted in each hole so that 160 Odot grass stek were needed. The method used in this study was an experimental method using a completely randomized design (CRD), consisting of 4 treatments and 5 repetitions namely P0 (100% Buffalo Feces), P1 (95% Buffalo Feces and 5% Chicken Feces), P2 (90% Buffalo Feces and 10% Chicken Feces), P3 (85% Buffalo Feces and 15% Chicken Feces). The data obtained in this study were then analyzed using Analysis of Variance (ANOVA). The results showed that the use of biogas sludge from different ratios of buffalo and chicken feces up to 15% had no significant effect (P0.05) on height, number of tillers, fresh and dry weight of Odot grass (Pennisetum purpureum cv. Mott).